Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s1090-3801(03)00014-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health‐related quality of life in patients with persistent somatoform pain disorder

Abstract: Patients with persistent somatoform pain disorder feel severely impaired. A clear pattern emerges for negative effects of the coping styles Increasing Pain Behaviors and Catastrophizing, while the identification of beneficial coping failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
(28 reference statements)
4
25
0
Order By: Relevance
“…The presence of a personality disorder is related to more severe overall psychopathology and a reduced level of functioning [12] . Petrak et al [3] found health-related quality of life of patients with SPD strongly and significantly reduced compared with the general population. Thomassen et al [17] reported a signifi cant decrease in employment rates of somatoform disorder patients from 58% in the group aged between 20 and 29 years to 6% in the group aged between 50 and 59 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a personality disorder is related to more severe overall psychopathology and a reduced level of functioning [12] . Petrak et al [3] found health-related quality of life of patients with SPD strongly and significantly reduced compared with the general population. Thomassen et al [17] reported a signifi cant decrease in employment rates of somatoform disorder patients from 58% in the group aged between 20 and 29 years to 6% in the group aged between 50 and 59 years.…”
Section: Introductionmentioning
confidence: 99%
“…Somatization has been defi ned as the tendency to experience and communicate somatic distress in response to psychosocial stress and seek medical help for it [1] . It is possible that in SPD there is a heightened awareness of normal bodily sensations and a cognitive misinterpretation of physical symptoms as pain and illness [2,3] . Hyperarousal states and altered central nervous system information processing might be involved in the somatization process.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that social support may figure as a coping assistance, and thereby result in increased activity levels [17]. Coping is associated with QOL, where strategies such as catastrophizing and avoidance are known to cause greater disruption of everyday life and negatively affect QOL [68,69]. The failure here to report an association between social support and physical QOL might be due to the relatively limited study period.…”
Section: Discussionmentioning
confidence: 72%
“…Patients with somatoform pain disorder were also considerably impaired in terms of their physical and mental quality of life. This finding was particularly true of patients with unfavorable defense styles, pronounced pain behavior, and tendencies to regard life events as catastrophes (Petrak, Hardt, Kappis, Nickel, & Egle, 2003).…”
mentioning
confidence: 92%